2001
DOI: 10.1002/1098-2396(20010301)39:3<257::aid-syn1007>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine self‐administration alters the morphology of dendrites and dendritic spines in the nucleus accumbens and neocortex

Abstract: We studied the influence of cocaine use on the structure of neurons in brain regions that contribute to its rewarding effects by allowing rats to self-administer cocaine (0.33 mg/infusion) for 1 h a day for 1 month. Control animals were left undisturbed or allowed to work for food for the same period of time. After an additional 1 month drug-free period the brains were processed for Golgi-Cox staining. In rats that self-administered cocaine, but not rats that worked for food, there was a significant increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
159
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(175 citation statements)
references
References 55 publications
14
159
1
1
Order By: Relevance
“…Repetitive administrations of cocaine to monkeys produced impairments of reversal learning that persist even after cessation of drug administration. Additional studies may indicate how drug-induced changes in cortical neuron morphology (Robinson and Kolb 1997;Robinson et al 2001), signal transduction mechanisms (Nestler and Aghajanian 1997), cortical-subcortical physiological interactions (Onn and Grace 2000) or excitatory amino acid and monoaminergic neurotransmission (Wolf 1998;Robbins and Everitt 1999;Berke and Hyman 2000;Vanderschuren and Kalivas 2000) contribute to this form of addiction-related psychopathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repetitive administrations of cocaine to monkeys produced impairments of reversal learning that persist even after cessation of drug administration. Additional studies may indicate how drug-induced changes in cortical neuron morphology (Robinson and Kolb 1997;Robinson et al 2001), signal transduction mechanisms (Nestler and Aghajanian 1997), cortical-subcortical physiological interactions (Onn and Grace 2000) or excitatory amino acid and monoaminergic neurotransmission (Wolf 1998;Robbins and Everitt 1999;Berke and Hyman 2000;Vanderschuren and Kalivas 2000) contribute to this form of addiction-related psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Volkow and Fowler 2000;London et al 2000). Second, chronic drug administration affects the neurochemistry and anatomy of these brain regions in animal models (Nestler and Aghajanian 1997;Robinson and Kolb 1997;Wolf 1998;Berke and Hyman 2000; Vandershuren and Kalivas 2000;Robinson et al 2001 (Post et al 1976), altered incentive motivation (Shippenberg and Heidbreder 1995;Taylor and Horger 1999;Robbins and Everitt 1999) and impaired cognitive and executive function (Jentsch et al 1997(Jentsch et al , 2000Rogers et al 1999;Robbins and Everitt 1999;Grant et al 2000;Ornstein et al 2000) after chronic stimulant drug administration.Because of its important role in decision-making (Bechara et al 2000) and inhibitory control over pre-potent behavior (Roberts and Wallis 2000), an involvement of ventromedial regions of the frontal cortex in drug abuse has been proposed. In essence, impairments of frontal lobe function are thought to effectively 'un-gate' subcortically-mediated, conditioned tendencies (such as established instrumental responses to obtain and consume drugs), resulting in the compulsive drug seeking and taking that characterize addiction (Jentsch and Taylor 1999).…”
mentioning
confidence: 99%
“…In all studies to date, both non-contingent and contingent cocaine or amphetamine administration were found to increase spine density, as well as dendritic branching on medium spiny GABAergic neurons within both the shell and core subregions of the NAC [198][199][200][201][202][203][204][205][206][207]. Similarly, repeated treatment with both psychomotor stimulants increase spine density and branching of the apical, and to a lesser extent the basalar, dendrites of glutamatergic pyramidal neurons within the PFC [198][199][200][201]204,205]. These structural data are consistent with greater levels of filamentous actin (Factin) within the NAC following both acute exposure to and withdrawal from repeated cocaine exposure [129].…”
Section: Potential Role For Homers In Drug-induced Alterations In Strmentioning
confidence: 98%
“…A recent study of the effects of chronic alcohol consumption (14 weeks exposure) revealed a number of dendritic abnormalities within the NAC, including a decrease in spine density, a thickening of the spine head and a disturbance in spine orientation [215]. Moreover, a subpopulation of medium spiny neurons also exhibited multi-headed spines (bifurcates and triplicates emerging from a common neck) and stacked-head spines, which resembled beads on a string with one head growing out of the other in serial arrangement [215] -abnormalities observed also following repeated psychomotor stimulant drug administration [205]. In both the case of the NAC and hippocampus, the alcohol-induced increases in dendritic spine head size was accompanied by increased synaptic targeting of NMDA receptors and clustering with PSD-95, as well as an enlargement in PSD-95-associated F-actin clusters [214][215][216].…”
Section: Potential Role For Homers In Drug-induced Alterations In Strmentioning
confidence: 99%
“…For example, repeated exposure to cocaine increases spine density on dendrites of dopaminoceptive medium spiny neurons in the shell (but not core) division of nucleus accumbens (NAc) (Robinson and Kolb, 1999;Robinson et al, 2001) and increases the expression of several transcription factors that mediate gene expression in these neurons (Nestler, 2001). Recently, cyclin-dependent kinase-5 (Cdk5) was identified as a downstream target of the transcription factor ΔFosB which is persistently expressed in NAc of mice repeatedly treated with cocaine.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%